Ultrasound Stimulation Modulates Voltage-Gated Potassium Currents Associated With Action Potential Shape in Hippocampal CA1 Pyramidal Neurons - Lin, Zhengrong; Huang, Xiaowei; Zhou, Wei; Zhang, Wenjun; Liu, Yingzhe; Bian, Tianyuan; Niu, Lili; Meng, Long; Guo, Yanwu (Frontiers in Pharmacology, 2019)
Potassium ion channels (K+) play an important role in the regulation of cellular signaling. Imbalance of potassium channels is associated with several severe ion channels diseases, such as long QT syndrome, episodic ataxia and epilepsy. Ultrasound stimulation has proven to be an effective noninvasive tool in the modulation of ion channels and neural activity. In this study, we demonstrate that ultrasound stimulation enables to modulate the potassium currents and has an impact on the shape of action potentials (AP) in the hippocampal pyramidal neurons using whole-cell patch-clamp recordings in vitro. The results shows that outward potassium currents in neurons increase significantly, approximately 13%, in response to the ultrasound stimulation with duration of 30s. Simultaneously, the increasing outward potassium currents directly decrease the resting membrane potential from -64.67 ± 1.10 mV to -67.51 ± 1.35 mV. Moreover, the threshold current and AP fall rate were increased while the reduction of AP half-width and after-hyperpolarization peak time were detected. With ultrasound stimulation, reduction of the membrane input resistance in pyramidal neurons could be found and shorter membrane time constant could be achieved. Additionally, we verify that the regulation of potassium currents and shape of action potential is mainly due to the mechanical effects induced by ultrasound. Therefore, ultrasound stimulation may offer an alternative to treat some ion channels diseases relative to potassium channels.